PERANCANGAN PENGEMBANGAN USAHA PERCETAKAN MENGGUNAKAN BUSINESS MODEL CANVAS PADA CV. KEDAI KAOS MAKASSAR - Riskawati; Nur Khaerani Busri; Iksan Adiasa; Fachriadi (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
CV. Kedai Kaos Makassar was established in 2013, which is one of the SMEs engaged in screen printing services where the raw materials are t-shirts. The problem that currently arises in the SME is the demand for custom products which is still difficult to fulfill and complete on time by the SME owner. The purpose of the study was to develop a printing business using the Business Model Canvas (BMC). The type of research used was qualitative research. The results of the study showed that to develop the printing business of CV. Kedai Kaos Makassar, what must be done is to add customer segments with communities, value proportions by producing their own production materials, adding channels to the website, key activities with convection machines and with additional costs for convection production and convection machine maintenance costs. Based on the results of the SWOT analysis, external and internal factors were obtained, namely strengths, weaknesses, opportunities and threats. The business development plan that must be carried out is to convect plain t-shirts that will be screen printed.